The Of Law Number 17 of 2023 in Improving the Quality of Service to Avoid Caries in Children’s Teeth In 2025 - Riri Ulfany; Irsyam Risdwati; Redyanto Sidi (CV. Era Digital Nusantara, 2026)
This study aims to analyze the role of Law Number 17 of 2023 in improving the quality of children’s dental health services in Indonesia, particularly in efforts to prevent dental caries. This law was introduced as part of healthcare policy reform to enhance children’s dental health services by emphasizing the importance of early prevention of dental diseases. The main focus of this study is to identify how the implementation of this policy can strengthen the dental healthcare service system in Indonesia in 2025. This research employs a qualitative approach by analyzing the policies stipulated in Law Number 17 of 2023 and examining their effectiveness in practical implementation. Improvements in the quality of children’s dental health services, especially in preventing dental caries, are expected to be achieved through enhanced healthcare facilities and infrastructure, public education, and training for healthcare personnel. With the enactment of this law, the government expects improvements in the management of dental healthcare services to become more effective and efficient. The study focuses on evaluating whether the policy can have a direct impact on reducing the prevalence of dental caries among children in 2025, as well as examining the role of healthcare workers in its implementation across various regions. The results of this study are expected to provide a clear overview of the effectiveness of Law Number 17 of 2023 in achieving the goal of preventing dental caries in children. This research is also expected to serve as a reference for policymakers in formulating more comprehensive and targeted follow-up policies to address children’s dental health issues in Indonesia in 2025.